Application of Breathing Relaxation Technique on Pain Management in Patients with Congestive Heart Failure (CHF) in the ICCU Ward of RSD Gunung Jati, Cirebon City - Syaripudin, Ahmad; Oktaviani, Fenty (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: The prevalence of heart disease in Indonesia, according to the 2018 Basic Health Research (Riskesdas), reached 1,017,290 cases, while in West Java Province there were 186,809 cases. To apply the intervention of deep breathing relaxation technique to Mr. A, a patient with congestive heart failure (CHF), focusing on pain management nursing care in the ICCU Ward of RSD Gunung Jati, Cirebon City. Method: This research used a case study design. The subject was one patient with CHF and pain management problems. Data collection methods included anamnesis, physical assessment, direct observation, and medical records. Nursing care was carried out for 3 days according to the shift schedule. Results: After applying deep breathing relaxation for three consecutive days, 10–15 minutes each session, the pain scale decreased from 6 (Numeric Rating Scale/NRS) to 2 (NRS). Conclusion: The application of deep breathing relaxation technique can reduce pain in CHF patients in the ICCU Ward of RSD Gunung Jati, Cirebon City.